Perempuan Nyurlembang Dalam Tradisi Merarik - Titi Fitrianita; Siti Kholifah; Rabiatul Adawiyah (SIMULACRA: JURNAL SOSIOLOGI, 2018)
Merarik is a tradition which has been maintained by Sasak since a long time. In the beginning, this tradition was an effort to save women from immorality of Anak Agung Made Karangasem, the king of Lombok. But the aim of this tradition started to change. This paper tries to analyze the change of merarik in Nyurlembang Village, Narmada, West Lombok. Using qualitative descriptive and feminist approach, this paper found that merarik causes cultural violence for women. In the middle of the merarik problem, proposal becomes a better alternative for women, but proposal not fully received because it is not their own culture.